Confessors carry the 'message of reconciliation' - Johannes Paul, II., Papst (Forum. A Review of Canon Law and Jurisprudence. Volume 16, 2005)
Es handelt sich um die Rede des Papstes an die Teilnehmer des Internationalen Forums